Accuracy of controlled attenuation parameter for assessing liver steatosis in individuals with morbid obesity before bariatric surgery. (20th December 2021) - Tavaglione, Federica; De Vincentis, Antonio; Bruni, Vincenzo; Gallo, Ida Francesca; Carotti, Simone; Tuccinardi, Dario; Spagnolo, Giuseppe; Ciociola, Ester; Mancina, Rosellina Margherita; Jamialahmadi, Oveis; D'Alessio, Rossella; Bottazzi, Bruna; et al.
Abstract: Background & Aims: The ultrasound‐based controlled attenuation parameter (CAP) is a non‐invasive tool widely validated for assessing liver steatosis across different etiologies. However, few studies, with liver biopsy available, have investigated its performance in individuals with morbid obesity. Herein, we aimed to evaluate the diagnostic accuracy of CAP in participants with morbid obesity from the MAFALDA study before bariatric surgery. Methods: A total of 120 individuals with valid examinations within three months from bariatric surgery were included. Clinical, laboratory, FibroScan ® (XL probe), and liver biopsy data were collected using standardized procedures. The overall accuracy of CAP for detecting liver steatosis was estimated by the area under the receiver‐operating characteristics curve (AUROC). Optimal cut‐offs were chosen at points with the highest Youden index. Results: The AUROCs of CAP for detecting S ≥ S1, S ≥ S2, and S = S3 were 0.91 (95% CI 0.86–0.97), 0.83 (95% CI 0.76–0.90), and 0.86 (95% CI 0.79–0.94), respectively. The best CAP cut‐offs for S ≥ S1, S ≥ S2, and S = S3 were 300 dB/m (95% CI 275–316), 328 dB/m (95% CI 296–345), and 344 dB/m (95% CI 343–352), respectively. CAP values were independently influenced by steatosis grade (estimate 20.60, 95% CI 12.70–28.40, P = 1.05 × 10 −6 ). The AUROC of FibroScan‐AST (FAST) score for detecting progressive non‐alcoholic steatohepatitis was 0.76 (95% CI 0.66–0.86). Conclusions: In individuals with morbid obesity, CAP measured by XL probe is an accurate non‐invasive tool for grading liver steatosis. Measurement of liver fat content by CAP may help identify those eligible for bariatric procedures and estimate the effect of bariatric surgery on hepatic steatosis. Lay Summary: The ultrasound‐based controlled attenuation parameter (CAP) by using the XL probe has an excellent performance for grading liver steatosis among individuals with morbid obesity. CAP may represent an accurate tool for the non‐invasive assessment of liver steatosis among individuals with morbid obesity before and after bariatric surgery.